Case report: Cerebral sinus vein thrombosis in VEXAS syndrome - Zisapel, Michael; Seyman, Estelle; Molad, Jeremy; Hallevi, Hen; Mauda-Havakuk, Michal; Jonas-Kimchi, Tali; Elkayam, Ori; Eviatar, Tali (Frontiers in Medicine, 2024)
VEXAS (vacuoles, E1 enzyme, X-linked, autoinflammatory, and somatic) syndrome is a newly described hemato-inflammatory acquired monogenic entity that presents in adulthood. One of the main features of VEXAS syndrome is a high venous thromboembolism (VTE) burden, with approximately 30–40% experiencing lower extremity deep vein thrombosis and a lower incidence of pulmonary embolism at approximately 10%. To date, VEXAS syndrome has not been associated with rarer forms of VTE such as cerebral sinus vein thrombosis (CSVT) and Budd–Chiari syndrome, which are well-recognized vascular manifestations in Behcet’s disease, another autoinflammatory vasculitic disease. Herein, we describe a case of acute severe extensive and fatal CSVT in a patient with VEXAS syndrome. The event occurred during a period of apparently quiescent inflammatory status, while the patient was receiving tocilizumab and a low dose of glucocorticoids. Despite treatment with anticoagulation, high-dose glucocorticoids, endovascular thrombectomy, and intracranial pressure-lowering agents, the patient suffered severe neurologic damage and ultimately succumbed to the condition 3 weeks after the onset of CSVT. To the best of our knowledge, this is the first reported case of CVST in a patient with VEXAS syndrome.